Jogos digitais no ensino da matemática para estudantes da educação de jovens e adultos: um estudo com estudantes das séries finais (Etapa IV - 7ª e 8ª série) numa escola municipal de Paço do Lumiar/Maranhão - SOUZA, Francisco Carlos Silva (2024)
The use of digital games in the teaching of mathematics to students of the final grades (Stage IV - 7th and 8th grades) of youth and adult education, carried out in a municipal school in Paço do Lumiar/Maranhão, aimed to investigate whether teaching through digital games would provide students with improved school performance in mathematics classes, as well as making them more stimulating, meaningful and interactive. It also serves as a basis for the elaboration of a pedagogical notebook, with methodological propositions that could subsidize the use of digital games, in a collaborative and dialogical way among the research subjects, contributing to the pedagogical practice of the teacher in the teaching of mathematics. The research began with: a) pedagogical meetings, b) application of questionnaires and c) interview with the students of the class in order to identify if the students knew the digital resources that would be used in the course of the investigation. With these data, it was decided to promote a workshop, together with the class teacher, with the application of games for the appropriation of the students' data. Then, the researcher, in a colorabor work, with the class teacher, developed with the students, several activities of teaching mathematics with the use of digital games. The survey revealed that students showed a lot of acceptance with the application of this teaching methodology. It was also observed that there was an improvement in school performance in mathematics classes. Thus, it was concluded that the investigation was relevant to the field of methodological knowledge aimed at the learning of the students involved in the research.